O acervo da Empresa Brasil de Comunicação (EBC): diagnóstico do serviço oferecido pela Central de Pesquisas e diretrizes visando ao seu aprimoramento - Hollanda, Fernanda Borges Buarque de (2019)
This work analyzes the service delivered to the external user of the Brazil Communication Company [Empresa Brasil de Comunicação, EBC] regarding the management of the TV and radio collection conducted by its Research Center and by other sectors which are responsible for the costly and non-costly assignment of the documents held by EBC. It identifies the main current obstacles of this service and proposes guidelines for the proper functioning of the Research Center, as well as actions for valuing EBC’s collection. In order to present the reader to the role of the Company, this work introduces the concept of public communication and presents some international experiences related to this communication modality.